Financial Sector Evolution in the Central European Economies : Challenges in Supporting Macroeconomic Stability and Sustainable Growth - Wagner, Nancy (IMF Working Papers; Working Paper, 2001)
This paper takes stock of the current state of development of the financial systems in five Central European transition economies (the Czech Republic, Hungary, Poland, the Slovak Republic, and Slovenia) that are also leading EU accession candidates. It presents both a progress report and an assessment of remaining challenges, with a focus on the role of the financial sector in supporting macroeconomic stability and sustainable growth.